TANTANGAN DAKWAH (Haruskah Dakwah Dipersulit Atau Dipermudah?) - Sunardi Bashri Iman; Retna Dwi Estuningtyas (LP2M IAI Muhammadiyah Sinjai, 2022)
In preaching, facing obstacles is a necessity. Barriers to many variants can come from an interpreter da'i or from the object of da'wah itself. The duty of a da'i must be able to overcome various kinds of da'wah problems. There are models of da'wah barriers that are innate in nature, intellectual abilities or lack of wisdom in applying ethics and aesthetics. This paper is a qualitative research, literature study with the main source base of classic da'wah science books with Arabic literature, also supported by the repertoire of Tsaqofah Islamiyah books. The secondary data are insights sourced from websites in the form of journal articles, newspapers or other sources. In conclusion, a da'i is required to act wisely in carrying out his da'wah mission. Simplifying is the solution, understand that other people have different backgrounds and life experiences. Make it easy by paying attention to the stages in conveying the mission, not overloading the task and trying to help reduce the burden he feels. It must also be noted that the methodology of da'wah, the use of methods and media in preaching, the task of a da'i is only to convey a message, not to give a decision, the mad'u must be on the right or wrong path. Just convey the results of da'wah in the power of Allah SWT.